Axiological Determinants of the Doctrine of “Living” in Modern Bioethic Discourse - Horban, Olexander; Martych, Ruslana (Studia Warmińskie, 2018)
The article is devoted to the presentation of the axiological determinants of the understanding of “life” in contemporary bioethical research. The authors note that the great social change is usually accompanied by a change in the understanding of certain values. The ongoing social changes demand people to find adequate answers to the challenges facing them. The authors also come to the conclusion that among the values around which there is currently a multifaceted discussion on their meaning is “life”. According to the authors, it turns out that, especially in the field of bioethics, it can be noticed that the suggested behavior towards living beings directly depends on the consciousness paradigm adopted in the given case.